An empirical test of TQM in public service sector and its impact on customer satisfaction - Arawati Agus (Penerbit ukm, 2005)
This article is based on the result of a TQM study aimed at investigating the relationship between TQM and customer satisfaction, as well as the strength of their manifest indicators. Several studies have proven that TQM practices have a significant positive impact on organizational performances. However, the impact of TQM on customer satisfaction in the service sector has not been fully addressed in empirical studies in Malaysia. To address this gap, this study seeks to enhance understandings of the relationships between TQM practices and customer satisfaction in a public service sector in Malaysia. Statistical methods used include reliability analysis, correlation analysis, a two-way ANOVA and structural equation modelling (SEM). The findings suggest that employee focus is a very important factor in TQM implementation in the service sector followed by training, customer focus, benchmarking, and top management commitment. The result also highlights the unique contribution of TQM towards customer satisfaction